THE ETHICS OF DA'WAH IN THE FAMILY ACCORDING TO AN ISLAMIC PERSPECTIVE - M Musthofa (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
The family is part of the community, a field for preachers to carry out preaching activities. This working paper aims to describe the ethics that must be used when da'wah is carried out in the family environment according to an Islamic perspective. The method used in this research is a literature review by outlining the example of the previous Prophets and Apostles that can be used as a model in building da'wah within the family in the current conditions. Based on the studies conducted, the Prophets and Apostles used the language of the people who were the object of da'wah so that they could understand it. The language in question also has a broad meaning, namely the customs or traditions that apply in society that do not come out of Islamic values ​​, so they accept them easily. Prophet Muhammad SAW. Used Arabic in preaching so that the Arabs quickly understood it. The following model is Prophet Ibrahim, who preached in the family using affection and without coercion. Exemplified in the Qur'an that preaching is an obligation that must be done well and without forcing it because its success is guidance determined by Allah SWT. Likewise, da'wah in the family environment must be carried out with good ethics.